Genome-Wide Analysis of Staphylococcus aureus Sequence Type 72 Isolates Provides Insights Into Resistance Against Antimicrobial Agents and Virulence Potential - Batool, Nayab; Shamim, Amen; Chaurasia, Akhilesh Kumar; Kim, Kyeong Kyu (Frontiers in Microbiology, 2021)
Staphylococcus aureus sequence type 72 is a major community-associated (CA) methicillin-resistant Staphylococcus aureus (MRSA) that has rapidly entered the hospital setting in Korea, causing mild superficial skin wound to severe bloodstream infections. In this study, we sequenced and analysed the genomes of one methicillin-resistant human isolate and one methicillin-sensitive human isolate of ST72 from Korea, K07-204 and K07-561, respectively. We used a subtractive genomics approach to compare these two isolates to other 27 ST72 isolates to investigate antimicrobial resistance and virulence potential. Furthermore, we validated genotypic differences by phenotypic characteristics analysis. Comparative and subtractive genomics analysis revealed that K07-204 contains methicillin (mecA), ampicillin (blaZ), erythromycin (ermC), aminoglycoside (aadD) and tetracycline (tet38, tetracycline efflux pump) resistance genes while K07-561 has ampicillin (blaZ) and tetracycline (tet38) resistance genes. In addition to antibiotics, K07-204 was reported to show resistance to lysostaphin treatment. K07-204 also has additional virulence genes (adsA, aur, hysA, icaABCDR, lip, lukD sdrC and sdrE) compared to K07-561, which may explain the differential virulence potential of these human isolates of ST72. Unexpectedly, the virulence potential of K07-561 was higher in an in vivo wax-worm infection model than that of K07-204, putatively due to the presence of a 20-fold higher staphyloxanthin concentration than K07-204. Comprehensive genomic analysis of these two human isolates, 27 ST72 isolates, and S. aureus USA300 (ST8) suggested that acquisition of both virulence and antibiotics resistance genes by ST72 isolates might have facilitated their adaptation from a community to a hospital setting where the selective pressure imposed by antibiotics selects for more resistant and virulent isolates. Taken together, the results of the current study provide insight into the genotypic and phenotypic features of various ST72 clones across the globe, providing more options for developing therapeutics and rapid molecular diagnostic tools to detect resistant bacteria.